Effect of Sodium Cyanide on Wheat (Triticum durum cv. Altar and T. aestivum cv. Cumhuriyet) - GEMICI, MELIHA; M. KARSHENASS, ARZU; TAN, KIT (Asian Journal of Chemistry, 2010)
The effect of sodium cyanide on the morphology of stem, leaves and grain yields of Triticum durum cv. Altar and Triticum aestivum cv. Cumhuriyet grown under glass was studied. Seeds were planted in six different sets of pots containing ordinary garden soil. After formation of the first leaves, the first set was used as the control and watered using ordinary bottled water sold commercially. The other five sets with T. durum cv. Altar and T. aestivum cv. Cumhuriyet seedlings were additionally watered with various concentrations of sodium cyanide, the test-quantity used being 10-50 mg/L. Growth of individual plants was monitored until grain production. It was found that the sodium cyanide concentrations in the feed solutions affected plant stature, with the plants becoming progressively dwarfed with increasing dosage. Anomalies in the morphological and anatomical structure of the plant were also noted, as was early ripening of grain and sterility.